Particle bombardment transformation of some Turkish wheat cultivars with TaNAC69-1 and TtNAMB2 genes - Battal, A.; Baloğlu, Mehmet Cengiz; Kavas, M.; Yücel, M.; Öktem, Hüseyin Avni (My University, 2012)
Wheat is one of the most important crop plants in the world. The production of wheat is seriously affected by biotic (pests, bacterial and fungal diseases) and abiotic (drought, salinity and freezing) stresses. NAC family proteins (NAM/ATAF1-2/CUC2) are plant specific transcription factors and related with development, defense and abiotic stress responses.
Keywords: NAC protein family; Transformation; Wheat; Particle